Translation, adaptation and psychometric testing of a tool for measuring nurses' attitudes towards research in Indonesian primary health care. Issue 2 (6th November 2016) - Rachmawati, Kurnia; Schultz, Tim; Cusack, Lynette
Abstract: Aim: The purpose of this study was to translate, adapt and psychometrically test the Nurses' attitudes towards and awareness of research and development within nursing (ATRAD‐N) version II for measuring nursing research and research utilization in Indonesian primary health care nurses. Design: Cross‐sectional survey. Method: The translation process was conducted by applying the forward and back‐translation method. Adaptation and content validity was assessed by six experts in Indonesia. The psychometric testing was performed using factor analysis and Cronbach's alpha coefficient on a sample of 92 primary health care nurses in South Kalimantan, Indonesia in 2013. Results: The translated instrument showed acceptable content validity with index of .97. The factor analysis (Principal Component Analysis with Direct Oblimin rotation) obtained a five‐factor structure that differed from those identified in previous studies. The cumulative percentage of variance was 56.5%. The Cronbach's alpha coefficient for individual factors ranged from .719 ‐ .884. The resulting form of the Indonesian ATRAD‐N was found to have acceptable content validity and homogeneity reliability but not construct valid in Indonesian settings.